Mechanism of Action of 2-Mercapto-1(β-4-pyridethyl)benzimidazole: A Reversible Inhibitor of Interferon Activity - Friedman, Robert M. (1970)
2-mercapto-1(β-4-pyridethyl)benzimidazole (MPB) inhibited the development of antiviral activity induced by interferon in chick cells. The MPB effect was reversed by washing the cells. The action of MPB was on a step immediately following interferon binding but before the cellular RNA and protein synthesis that appear to be required for interferon action. The step blocked by MPB possibly involves cellular phospholipid synthesis.